"To Tell Or Not To Tell?" : Incorporating Disclosure And Privacy Requirements In Web Portal Design For Malaysian Cancer Patients. - Zakaria, Nasriah (2007)
Cancer patients need to disclose their health information to their disclosure network: a group of people who patients disclose sensitive health information. The disclosure process can be done using oral as well as communication technologies like telephone and the Internet.